Hubungan Pengetahuan dan Sikap Ibu terhadap Pelaksanaan Pijat Bayi di PMB Muzilatul Nisma Kota Jambi - Selpyani Sinulingga; Sirly Patriani (Universitas Baiturrahim, 2023)
Baby care in health sciences, especially midwifery, there is many of kinds that use to maintain the health of babies from newborns to 12 months of age. One of baby care is baby massage. Baby massage is an art of health care that is touch therapy with specialy techniques that given to babies there for the benefits of treatment and health are achieved. This research is quantitative with cross sectional approach. The purpose of this study was to determine the relationship between mother's knowledge and attitudes towards the implementation of infant massage for infants 0-12 months at PMB Muzilatul Nisma Jambi City. The data collection of mother's knowledge and attitudes towards the implementation of infant massage was collected by a questionnaire. The population in this study were all mothers with babies 0-12 months who visited PMB Muzilatul Nisma totaling 80 people with a sample of 45 peoples. The sampling technique is accidental sampling. Data analysis was carried out univariate and bivariate using chi square statistical test. The results showed that there was a relationship between knowledge and massage in infants aged 0-12 months with p-value = 0.039. Beside that, there is a relationship between mother's attitude and baby massage in infants aged 0-12 months with a P-value = 0.012. From the results of this study, it is hoped that health workers and midwifery service providers will be more active in providing education to the public about baby massage.